Evaluating the impact of COVID-19 on cancer care: a comprehensive analysis of treatment modifications, risk factors, and patient outcomes - Xuquan Jing; Min Wang; Shuangqing Lu; Jiling Niu; Feihu Chen; Hanjing Yin; Haoyu Liu; Dongmei Sun; Hui Zhu (BMC Infectious Diseases)
Abstract Background Cancer patients will have an increased incidence of corona virus disease 2019 (COVID-19) infection. The severity of COVID-19 infection varies among cancer patients who have other complications and are being treated. Method This retrospective cohort study evaluated the impact of cancer treatments on COVID-19 incidence and outcomes in 603 cancer patients. Key objectives included assessing treatment-related risks, severity, and treatment efficacy, along with the effects of treatment interruptions on patient recovery and therapy resumption. Result This study included 603 cancer patients, of whom 68 (11.28%) were infected with COVID-19, and 398 (66%) were vaccinated. Logistic regression analysis revealed that underlying comorbidities, chemotherapy, and radiotherapy were significantly associated with an increased risk of COVID-19 infection (P < 0.05 for chemotherapy and radiotherapy). Factors such as sex, smoking status, cancer pathology, and staging showed no significant correlation with COVID-19 incidence. Treatment disruptions during the pandemic were observed, with chemotherapy being most affected (42.86% suspension), while surgery and TKI therapy showed minimal interruption. Efficacy analysis indicated no significant difference in treatment outcomes between suspended and uninterrupted treatments (P = 0.758). Treatment suspensions did not significantly alter toxicity profiles, with bone marrow suppression being the most frequent toxicity. Conclusion Chemotherapy and radiotherapy increased the risk of COVID-19 in cancer patients, with treatment interruptions not affecting efficacy or toxicity, underscoring the need for tailored management.